Evaluasi dan Strategi Pengembangan Bisnis Berbasis Greenpreneurship pada Brand Fashion Tote Bag (Raventive) - Kautsar Rafa Nusaibah; Mochamad Malik Akbar Rohandi; Rezi Muhamad Taufik Permana (Bandung Conference Series: Business and Management, 2024)
Abstract . The existence of digitization in the fashion industry makes people’s interest in the world of fashion continue to grow and develop. The high interest of the community makes business actors continue to produce products without considering the impact, especially on the environment, where this phenomenon is commonly called fast fashion. Raventive is a fashion business brand that prioritizes functional, stylish and environmentally friendly tote bag products. Raventive has a greenpreneurship concept where all production processes, products and packaging used are environmentally friendly. With tight business competition, Raventive needs to increase brand popularity and develop business by reviewing several aspects. Raventive uses the SWOT Analysis method, Porter's Five Forces, Balance Scorecard, Target and Performance, and Boston Consulting Group (BCG) Matrix in evaluating and creating business development strategies. From the results of the evaluation, there are several strategies that Raventive can do to develop products that are divided into the short term, namely being selective in choosing raw materials, increasing marketing and being consistent in financial records. Meanwhile, in the medium term, brands need to increase product innovation, conduct product manufacturing training and look for alternative production partners. Then in the long term, brands need to start opening up jobs, making bag care products and starting to invest in equipment. Abstrak. Adanya digitasisasi pada industri fashion menjadikan minat masyarakat terhadap dunia fashion terus tumbuh dan berkembang. Tingginya minat masyarakat menjadikan para pelaku bisnis terus memproduksi produk tanpa melihat dampak yang ada khususnya pada lingkungan yang dimana fenomena ini biasa disebut dengan fast fashion. Raventive merupakan brand usaha di bidang fashion yang mengutamakan produk tote bag yang functional, stylish dan environmental friendliness. Raventive memiliki konsep greenpreneurship dimana segala proses produksi, produk dan packaging yang dipakai ramah lingkungan. Dengan persaingan bisnis yang ketat, Raventive perlu meningkatkan popularitas brand dan mengembangkan bisnis dengan meninjau beberapa aspek. Raventive menggunakan metode SWOT Analysis, Porter’s Five Forces, Balance Scorecard, Target and Perfomance, dan Boston Consulting Group (BCG) Matrix dalam mengevaluasi dan membuat strategi pengembangan bisnis. Dari hasil evaluasi tersebut terdapat beberapa strategi yang dapat dilakukan Raventive untuk mengembangkan produk yang terbagi dalam jangka pendek yaitu selektif dalam pemilihan bahan baku, meningkatkan pemasaran dan konsisten dalam pencatatan keuangan. Sementara itu dalam jangka menengah brand perlu meningkatkan inovasi produk, melakukan pelatihan pembuatan produk dan mencari alternatif mitra produksi. Kemudian dalam jangka panjang brand perlu mulai membuka lapangan pekerjaan, membuat produk perawatan tas dan mulai berinvestasi dalam peralatan.